The Impact of Tax Planning on Earnings Management in Manufacturing Firms: Dampak Perencanaan Pajak terhadap Manajemen Laba pada Perusahaan Manufaktur - Qusna, Asmaul; Widodo, Heri (Indonesian Journal of Law and Economics Review, 2024)
General Background: Tax planning is a legal strategy employed by taxpayers to minimize their tax liabilities through effective utilization of existing tax laws, ultimately enhancing taxation efficiency. Specific Background: Tax planning's direct impact on earnings management in manufacturing firms, especially in emerging markets like Indonesia, is still underexplored despite its importance. Knowledge Gap: Previous studies have primarily examined the correlation between tax planning and financial performance, neglecting the moderating influence of firm value. Aims: The study examines the influence of tax planning on earnings management in manufacturing companies listed on the Indonesia Stock Exchange from 2017-2020, considering firm value as a moderating factor. Results: Utilizing a quantitative, associative research methodology and secondary data from IDX, the analysis revealed that tax planning significantly affects earnings management (significance level: 0.008), confirming the first hypothesis. Furthermore, the findings indicate that firm value positively moderates the relationship between tax planning and earnings management (significance level: 0.000), thus supporting the second hypothesis. Novelty: This study bridges the gap between tax planning, earnings management, and the moderating effects of firm value in a developing economy. Implications: The study highlights the importance of strategic tax planning for manufacturing firms to improve earnings management, emphasizing the need for firm value consideration in tax-related decision-making. Highlights: Tax planning significantly impacts earnings management in manufacturing firms. Firm value moderates the relationship between tax planning and earnings management. Utilizes quantitative research with secondary data from IDX website. Keywords: tax planning, earnings management, firm value, manufacturing companies, Indonesia Stock Exchange